Smart Learning Ecosystems in Transition: A Systematic Review on the Adoption of ICT and IoT as Emerging Technologies in Education (Architecture Image Studies, 2025)
This systematic literature review investigates the integration and adoption of Information and Communication Technology (ICT) and the evolving role of the Internet of Things (IoT) in the field of education. Utilizing thirty peer-reviewed empirical studies published from 2020 to 2025 and using the PRISMA protocol, this systematic literature review provides a comprehensive synthesis of the evidence across various educational levels and global contexts. Evidence related to technology adoption rates demonstrated similar and consistent patterns and included key determinants of technology adoption. Overall, although the findings demonstrated that ICT and IoT have potential valued implied and explicit student engagement, the shifting mindset required to create innovative pedagogy and professional learning to ultimately effect learning outcomes is plagued by the usual barriers in education. Some of the barriers include the limited confidence and competence of some teachers, limited technology infrastructure, funding, time, resistance to change, and limited engagement with digital sustainability. Differences in 'adoption' because of age, gender or teaching experience were described. It would be beneficial if the education sector adopted a multi-stakeholder approach to the integration of sustainable technology, which included tailored and continuous professional development, institutional support, participatory policy development and environmental steward accountability. The suggested future research should incorporate mixed-method approaches, involve a wider range of stakeholders and assess the long-term educational implications of adopting use of ICT and IoT.